RIPK1 ensures intestinal homeostasis by protecting the epithelium against apoptosis - Takahashi, Nozomi; Vereecke, Lars; Bertrand, Mathieu J. M.; Duprez, Linde; Berger, Scott B.; Divert, Tatyana; Goncalves, Amanda; Sze, Mozes; Gilbert, Barbara; Kourula, Stephanie; Goossens, Vera; Lefebvre, Sylvie; et al. (Nature, 2014)
Receptor interacting protein kinase 1 (RIPK1) has an essential role in the signalling triggered by death receptors and pattern recognition receptors. RIPK1 is believed to function as a node driving NF-?B-mediated cell survival and inflammation as well as caspase-8 (CASP8)-dependent apoptotic or RIPK3/MLKL-dependent necroptotic cell death. The physiological relevance of this dual function has remained elusive because of the perinatal death of RIPK1 full knockout mice. To circumvent this problem, we generated RIPK1 conditional knockout mice, and show that mice lacking RIPK1 in intestinal epithelial cells (IECs) spontaneously develop severe intestinal inflammation associated with IEC apoptosis leading to early death. This early lethality was rescued by antibiotic treatment, MYD88 deficiency or tumour-necrosis factor (TNF) receptor 1 deficiency, demonstrating the importance of commensal bacteria and TNF in the IEC Ripk1 knockout phenotype. CASP8 deficiency, but not RIPK3 deficiency, rescued the inflammatory phenotype completely, indicating the indispensable role of RIPK1 in suppressing CASP8-dependent apoptosis but not RIPK3-dependent necroptosis in the intestine. RIPK1 kinase-dead knock-in mice did not exhibit any sign of inflammation, suggesting that RIPK1-mediated protection resides in its kinase-independent platform function. Depletion of RIPK1 in intestinal organoid cultures sensitized them to TNF-induced apoptosis, confirming the in vivo observations. Unexpectedly, TNF-mediated NF-?B activation remained intact in these organoids. Our results demonstrate that RIPK1 is essential for survival of IECs, ensuring epithelial homeostasis by protecting the epithelium from CASP8-mediated IEC apoptosis independently of its kinase activity and NF-?B activation.
EVALuna2:1912